Extreme Growth Increments Reveal Local and Regional Climatic Signals in Two Pinus pinaster Populations - Vieira, Joana; Nabais, Cristina; Campelo, Filipe (Frontiers in Plant Science, 2021)
Tree rings are valuable proxies of past climate that allow inferring past growth responses to climate variability and extremes events, which is only possible considering that the relationship between tree growth and environmental conditions is linear and stable over time. However, in the last decades, divergent growth patterns have been observed in trees from the same forest stand, while unprecedented growth convergence was observed between trees from distant locations. Here, we use a new approach that considers convergent and divergent event years in two populations of Pinus pinaster Aiton in an altitudinal and oceanic-continental gradient to investigate what is triggering divergence and convergence in tree growth. The two study sites are Tocha, a plantation on sand dunes at low altitude near the ocean, and Serra da Estrela, a mountain plantation located at 1100 m altitude, 100 km away from the ocean. The analysis of the climatic conditions in convergent growth years revealed that positive convergent growth was related to above average precipitation in previous winter and that negative convergent growth was related to below average precipitation during the growing season. Divergent growth revealed a temperature signal with warmer temperatures in spring promoting growth in Serra da Estrela and growth reduction in Tocha. Convergent growth was associated to a regional climatic signal, reinforcing the importance of precipitation in the Mediterranean region, and divergent growth to a local temperature signal. Our findings suggest that under future climate change scenarios, where temperature is predicted to rise and precipitation to decrease, Serra da Estrela trees are expected to increase growth whenever water shortage does not override the temperature effect, and Tocha trees are expected to decrease growth in response to precipitation reduction. The information gathered in this study gives valuable insights on the response of P. pinaster to extreme climatic events, allowing for more adjusted management strategies of Mediterranean pine forests.